Peningkatan pengetahuan guru dan orang tua siswa taman kanak-kanak tentang penggunaan suplemen vitamin yang tepat - Binar Asrining Dhiani; Siti Nurjanah; Narendra Istia Putri; Ihza Ihtimamul Umam (University of Islam Malang, 2021)
COVID-19 global pandemic increases the usage of vitamin supplement products. However, easy access to purchase and consume the product increases the risk for its misuse. Lack of information and or misinformation available for vitamin supplement product usage leads to its abuse. Teachers' and parents' role in deciding the choice and use of vitamin supplement products for the pupil and children is crucial. Thus, a program was held to provide information about the correct usage of vitamin supplement products for teachers and parents. The program was performed for the teachers and pupil parents of TK Aisyiyah Ledug via online. The attractive audio-visual program materials were delivered via animation video, artistic leaflet, and presentation. The teachers and parents responded positively toward the program. All attendants actively participated, and 100% of attendants agreed that the program was interesting and increased their knowledge on the appropriate usage of vitamin supplement products.